2008
DOI: 10.1289/ehp.10353
|View full text |Cite
|
Sign up to set email alerts
|

HPRT Mutations in Lymphocytes from 1,3-Butadiene-Exposed Workers in China

Abstract: Background1,3-Butadiene (BD) is an important industrial chemical and an environmental and occupational pollutant. The carcinogenicity of BD in rodents has been proved, but its carcinogenic and mutagenic molecular mechanism(s) are not fully elucidated in humans.ObjectivesIn the present study, we compared the mutation frequencies and exon deletions of BD-exposed workers with that of control subjects in China to identify the characteristic mutations associated with BD exposure in the human HPRT (hypoxanthine–guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Using CBMN cytome assay, our study shows that BD exposure could induce chromosomal damage (MNi and NPBs) in BD-exposed workers, which was consistent with two other studies in China [ 10 , 16 ]. However, several studies have yielded negative results [ 6 9 ]. Individual differences especially genetic polymorphisms may contribute such inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using CBMN cytome assay, our study shows that BD exposure could induce chromosomal damage (MNi and NPBs) in BD-exposed workers, which was consistent with two other studies in China [ 10 , 16 ]. However, several studies have yielded negative results [ 6 9 ]. Individual differences especially genetic polymorphisms may contribute such inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of common genotoxic endpoints, only a few studies have yielded positive results. For example, one group studied the population in Texas in the US and reported significantly elevated frequencies of hypoxanthine-guanine phosphoribosyltransferase ( HPRT ) gene mutations in the peripheral blood lymphocytes (PBLs) of BD-exposed workers [ 5 ], while others failed to find increases in gene mutations [ 6 9 ]. For chromosome-level damage, a study in China [ 10 ] indicated positive induction of micronucleus (MN) in the PBLs of heavily exposed BD workers, but similar cytogenetic effects have not been indicated by several studies conducted on BD-exposed workers in Italy and the Czech Republic [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, the annual production volume of BD was over 1.41 million tons in 2008, and was estimated to have reached nearly 2.77 million tons annually by 2012 [2]. BD exposure is a critical public health concern because of its carcinogenicity [1,3,4]. Epidemiological studies have shown that occupational exposure to BD is associated with increased mortality from leukemia [6][7][8] and other hematopoietic malignancies [5].…”
Section: Introductionmentioning
confidence: 99%
“…In another study in China, a higher but not statistically significant increase in hprt mutation frequencies was observed among petrochemical workers exposed to mean levels of butadiene of 10 ppm. In addition, the frequency of exon deletions in butadiene-exposed workers was significantly higher than that in control subjects (564).…”
Section: Clinical Casesmentioning
confidence: 75%